SISTEM INFORMASI PENJUALAN PAKAN HEWAN BERBASIS WEB PADA TOKO SAZAHRN_STUFFCOLLECTION - Maulana Assyidiq (2022)
The website information system is one of the important things in a store's needs. Sazahrn_StuffCollection is an animal feed store for land, sea, and air animals that requires a website-based information system because the dissemination of information and the purchasing process still uses a manual system. To meet these needs, it is necessary to develop website-based technology. In addition to preventing file loss, it takes a long time and the dissemination of information that is still inadequate can help stores more easily manage this. In developing the system, the researcher made a research flow and identified problems with the PIECES method to match the needs of the system developed through observation to the store. The information system was created using Visual Studio Code in coding and using the Laravel & Bootstrap framework to assist researchers in creating an attractive display. It is hoped that this system can be the right alternative to be a solution to the problems experienced by the store.